Safety and efficacy of a unique scleral flap in mitomycin C-augmented trabeculectomy over one year - En-Jie Shih; Ying-Ying Chen (Scientific Reports, 2025)
Abstract This study introduced a modified trabeculectomy method and compare its effectiveness and safety to prior studies. Twenty-seven glaucoma patients (32 eyes) underwent mitomycin C-augmented trabeculectomy with a unique scleral flap shape at Kaohsiung Veterans General Hospital. The IOP decreased significantly from baseline (28.80 ± 11.37 mm Hg) to postoperative day 1, week 1, week 2, week 4, week 6, month 3, month 6, and year 1 (range, 14.10 ± 5.90 to 17.80 ± 5.14 mm Hg; all p < 0.05). The antiglaucoma medication use also decreased significantly from baseline (n = 4.72 ± 1.25) to 1 year after trabeculectomy (n = 0.75 ± 1.37) (p < 0.001). No surgical failures or glaucoma reoperations occurred during follow-up. Early complications and interventions included bleb encapsulation (n = 3, 9.38%), bleb leaks (n = 3, 9.38%), and needling revision (n = 1, 3.13%). Late complications and interventions included bleb encapsulation (n = 2, 6.45%), needling (n = 5, 16.13%), and cataract extraction (n = 2, 6.45%). Our trabeculectomy method with a modified scleral flap shape has demonstrated comparable success rates and improved safety compared to existing techniques. However, as this is a retrospective study, further randomized controlled trials are needed to draw definitive conclusions regarding its superiority or comparability.